High Levels of IL-18 and IFN-γ in Chronically Inflamed Tissue in Chronic Granulomatous Disease - Meda Spaccamela, Virginia; Valencia, Rocio G.; Pastukhov, Oleksandr; Duppenthaler, Andrea; Dettmer, Matthias S.; Erb, Juliane; Steiner, Urs C.; Hillinger, Sven; Speckmann, Carsten; Ehl, Stephan; Reichenbach, Janine; Siler, Ulrich (Frontiers in Immunology, 2019)
Background: Chronic Granulomatous disease (CGD) is caused by a malfunctioning nicotinamide adenine dinucleotide phosphate (NADPH) oxidase complex in phagocytes, leading to impaired bacterial and fungal killing and hyper-inflammation. Objective: To characterize macrophage subsets and cytokine/chemokine signaling loops involved in CGD tissue hyper-inflammation. Methods: Cytokine/chemokine production and surface marker expression were analyzed in inflammatory tissue of four CGD patients and compared to cytokine/chemokine released by CGD macrophages upon priming to different macrophage subpopulations. Furthermore, the re-priming capacity of CGD pro-inflammatory M1 to M2a anti-inflammatory macrophages was evaluated. Results: In human CGD inflammatory tissue, IL-18 and IFN-γ were detected in significant quantity. Immunofluorescence analysis identified macrophages as one source of IL-18 in inflamed tissue. In vitro, CGD macrophages could be primed and re-primed into all inflammatory/anti-inflammatory macrophage subpopulations. IL-18 was also released by M1 CGD and control macrophages. Conclusion: CGD pro-inflammatory M1 macrophages remain M1 primed in vivo. As CGD M1 macrophages can be re-primed to anti-inflammatory M2a phenotype in vitro, macrophages are kept in M1 state in vivo by a persistent pro-inflammatory environment. Our results suggest a paracrine signaling loop between M1 macrophage derived IL-18 and non-macrophage derived IFN-γ maintaining macrophage pro-inflammatory activity in CGD tissue.